Epidemiological Study of Chronic Kidney Disease in A Tertiary Care Hospital (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: Chronic Kidney Ddisease (CKD) diagnosed with objective measures of kidney damage and function has been recognised as a major public health burden worldwide. Independent of age, sex, ethnicity and comorbidity, strong associations exist between cardiovascular diseases, mortality morbidity with CKD. Detection of CKD within the population is therefore a priority for health systems. To evaluate etiology, common clinical presentations and laboratory findings of Chronic Kidney Disease (CKD) and to raise the index of clinical suspicion so to diagnose and treat CKD at the earliest.Materials and methods : This is a retrospective observational study carried out at CMH Dhaka. We had collected documents of 100 hospital patients of CKD (Stage- 3,4,5) who were admitted at Nephrology Center, Combined Military Hospital (CMH) Dhaka from 1 July 2013 to 31 May 2014. Clinical and laboratory data were collected from case sheets and attached lab results.Results: Out of 100 patients, 69.0% (n=69) were male and female were 31.0% (n=31). Male to female ratio was 2.2:1. Mean age was 45.64 years (±12.89 SD). Majority 37(37.0%) patients had diabetic nephropathy, 24(24.0%) had hypertensive nephropathy, 23(23.0%) had chronic glomerulonephritis. On the basis of creatinine clearance majority (50%) were CKD stage- 3. Mean urinary albumin- creatinine ratio were 634.4 mg/g (CKD stage- 3) 1965 mg/g (CKD stage- 4) and 2831.20 mg/g (CKD stage- 5). Eighty one percent (81%) of the patients had their hemoglobin level in the range of 8-9 gm/dl. Sixty five percent (65%) had the potassium within normal limits (3.5-5 meq/l) and 35% had hyperkalemia. We found anemia (86%), HTN (75%), oliguria (73%), pedal edema (70%), vomiting (44%), anorexia (30%), generalized weakness (28%), facial edema (24%), breathlessness (12%) were common clinical features.Conclusion Diabetes, hypertension and glomerulonephritis are the most common etiological conditions of CKD. Most patients are anemic and a significant number of them develop hyperkalemia. At the time of diagnosis most of the patients are in advanced state with CKD stage- 3 or more with shrunken kidneys.JCMCTA 2019 ; 30 (2) : 75-80